Wireless EEG Signal Transmission Using Visible Light Optical Camera Communication - Aggarwal, Geetika; Dai, Xuewu; Binns, Richard; Saatchi, Reza; Busawon, Krishna; Bentley, Edward (Applications of Computing and Communication Technologies, 2018)
Electroencephalogram (EEG) has been widely adopted for the brain monitoring. The transmission of the EEG signals captured from the scalp using electrodes to a displayed screen is often performed through wires utilizing Radio Frequency (RF) communication technology. The wired EEG transmission restricts the patient movement during the entire EEG recordings. However, patient movement is necessary during EEG recordings in certain medical scenario. Towards this end, wireless transmission of the EEG signals enables patient movements during the recordings. In this context, this paper proposes a Visible Light Optical Camera Communication (VL-OCC) system for wireless transmission of EEG signal. The signal transmission under the LOS, line of sight is conducted modulation scheme namely On-Off-Keying (OOK), Non-Return-to-Zero (NRZ). Specifically, organic light emitting diode, and optical camera are used as sender and receiver in the system, respectively. The performance of VL-OCC system is evaluated by developing an experimental prototype under realistic medical scenario.